Socio-political identity in Chosŏn Korea during the Japanese and Manchu invasions 1567-1637: Barbarians at the gates - Quartermain, TNDE (2016)
This thesis explores social and political identities in Chosŏn Korea between the years 1567 and 1637, particularly during the Imjin War (1592-1598) and the Manchu Invasions (1627 and 1636-1637). During the Imjin War, the Japanese caused widespread destruction over the entire Korean peninsula and the Ming army entered the country. The Later Jin briefly invaded in 1627 and launched a large scale invasion in 1636. The Manchus overran Chosŏn’s feeble defenses and forced Chosŏn to become a vassal state of the Qing Empire. Scholars are at odds over the form of socio-political identity during this period of foreign invasion. Some claim these wars created the 'Korean nation' for the first time, while others contend that no such socio-political concepts could have existed before the twentieth century. However, researchers often use the same philosophical approaches and merely select aspects of certain theorists' frameworks that best support their arguments. Both the theories and historian's methodologies are limited in their explanation of socio-political identity of the premodern Korean past and even more so for the time of the Imjin and Manchu Invasions. My research attempts to solve these theoretical problems by creating a 'fusion of horizons' between past and modern concepts of socio-political identity in order to explore the political and cultural environments of the Chosŏn people before and during the wars (bildung). This is achieved firstly by relying on official government histories and individually written diaries that, together, create a more complete picture of former socio-political identity. Secondly, I propose understanding Chosŏn by looking at the definitions of the king, state, people, culture, history, and foreign world using their own definitions from their own times.